STUDY OF COMPRESSIONAL AND SHEAR WAVE VELOCITY TESTS IN THE LABORATORY AND FIELD APPLIED TO SEDIMENTARY ROCKS OF RANTAU NANGKA DISTRICT, SOUTH KALIMANTAN - Zulfahmi Zulfahmi (Puslitbang tekMIRA, 2013)
Compressional (Vp) and shear (Vs) wave velocities within rocks are often investigated by testing in the laboratory because it is easier and cheaper. However, it is more confidence with investigation results derived from the field due to the actual situation and conditions. In the laboratory, the wave velocities are commonly measured using ultrasonic pulse velocities test. But in the field, the velocities are commonly measured directly by several methods such as cross-hole seismic, down-hole seismic, suspension logging, seismic reflection, seismic refraction and spectral analysis of the surface wave. In the present study of field insitu tests, it has used down-hole seismic method. The field insitu test is more expensive than the laboratory test. Hence, this study would evaluate and compare data derived from both of laboratory and field insitu tests. Based on the measurements correlation, it is found that regression equation for each parameter are ... for compressional wave velocities, ... for shear wave velocities, xxxxx for shear modulus, ... for ... modulus of elasticity, for bulk modulus and ... for Lame constants. This equation can be applied to correct the laboratory test data in order to get close results between the laboratory and field insitu tests.